The Effect of the STEM-PBL Learning on Students’ Learning Outcomes on Optical Concepts - Rohali, Putri Alayda; Qadar, Riskan; Syam, Muliati (International Journal of STEM Education for Sustainability, 2023)
This study aimed to determine the effect of STEM learning on Optical material on student learning outcomes at junior high schools. This study used a quantitative approach using a one-group pretest-posttest design. The population is the entire class of one of the junior high schools in Samarinda, Indonesia, with the sampling technique using random cluster sampling, which is only one class with a total of 31 students from class VIII. Data collection in this study uses test techniques to determine student learning outcomes. Data were analyzed using Paired Samples t-Test. The study showed a significant effect of STEM learning on learning outcomes. It was demonstrated based on the average value of learning outcomes which increased from 11.70 to 53.87, and the significance value of the paired sample t-test, which was smaller than 0.05, which was equal to 0.000 with an N-Gain test of 0.47, including the moderate category.